2006
DOI: 10.1128/iai.00546-06
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Genomic Plasticity in Pseudomonas aeruginosa Revealed by Identification and Distribution Studies of Novel Genes among Clinical Isolates

Abstract: The distributed genome hypothesis (DGH) states that each strain within a bacterial species receives a unique distribution of genes from a population-based supragenome that is many times larger than the genome of any given strain. The observations that natural infecting populations are often polyclonal and that most chronic bacterial pathogens have highly developed mechanisms for horizontal gene transfer suggested the DGH and provided the means and the mechanisms to explain how chronic infections persist in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 59 publications
(60 reference statements)
2
70
0
1
Order By: Relevance
“…In many cases, this genetic variation results in altered expression of virulence factors or a loss altogether of genes encoding certain virulence determinants (51)(52)(53). To date, all sequenced isolates of P. aeruginosa possess the tandem arrangement of the prrF genes (71), indicating that the region encoding both the PrrF and PrrH sRNAs is part of the core genome of this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, this genetic variation results in altered expression of virulence factors or a loss altogether of genes encoding certain virulence determinants (51)(52)(53). To date, all sequenced isolates of P. aeruginosa possess the tandem arrangement of the prrF genes (71), indicating that the region encoding both the PrrF and PrrH sRNAs is part of the core genome of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the plasticity of the P. aeruginosa genome, resulting in highly variable expression of virulence factors in differ- ent strains (51)(52)(53). We therefore determined the ability of several P. aeruginosa laboratory strains and clinical isolates to express and regulate the PrrF and PrrH sRNAs in response to iron and heme.…”
Section: Figmentioning
confidence: 99%
“…The effect of bacteriophages on populations is, as yet, unclear, but it has been shown that bacteriophages can drive diversification [64]. Extensive genome plasticity has been reported for P. aeruginosa clinical isolates, with phage sequences contributing to horizontal gene transfer and sequence diversity [65]. Furthermore, the presence of bacteriophages has been shown to present difficulties for some typing methods.…”
Section: Microbiological and Genomic Characteristics Of The Lesmentioning
confidence: 99%
“…As shown for Haemophilus influenzae, P. aeruginosa, Streptococcus pneumoniae, and other bacterial pathogens, there is considerable variation in the DNA content of each isolate (18,29,41,42). The accessory genome of A. baumannii comprises 2,649 annotated genes that are present in one to five of the six isolates.…”
Section: Genomesmentioning
confidence: 99%